SEBARAN PESUT (Orcaella brevirostris) DI PERAIRAN KABUPATEN KUBU RAYA DAN DI PERAIRAN KABUPATEN KAYONG UTARA PROVINSI KALIMANTAN BARAT - Purnomo, Adi; Rifanjani, Slamet; Wahdina, . (JURNAL HUTAN LESTARI, 2017)
Porpoises or freshwater dolphins (Orcaella brevirostris), of Delphinidae family and is a kind of marine mammals. Porpoises are one of oceanic dolphins biota but this group can live in the sea, brackish or fresh water. This species distributed in the shallow waters of tropical and subtropical Indo-Pacific from northern Australia waters, Papua New Guniea, to the Bengal Bay, especially in Brahmaputra and Ganges of India River waters, mekong in Vietnam, Laos and Cambodia, the Mahakam River in East Kalimantan and Ayeyarwady river in Myanmar. This study is aimed to determine the distribution of the dolphins (Orcaella brevirostris) in the waters kubu raya district and waterways Kayong utara districts. This study uses survey / observation method, population observation method using cruising with a ship. The survey results were the discovery of the dolphins numbered 13 tails and are in three different groups. The first group was found in simpang lidah area. Kubu Raya district 9 tails, the second group was found in Paket 3 (Batu Ping). Kayong Utara District 2 tails and a third group in bumbun estuaries. Kubu Raya District 2 tails. Keyword: District Kubu Raya, District Kayong Utara Waters. Pesut (Orcaella brevirostris)